2017
DOI: 10.3390/ijms18071420
|View full text |Cite
|
Sign up to set email alerts
|

Independent Preharvest Applications of Methyl Jasmonate and Chitosan Elicit Differential Upregulation of Defense-Related Genes with Reduced Incidence of Gray Mold Decay during Postharvest Storage of Fragaria chiloensis Fruit

Abstract: The Chilean strawberry (Fragaria chiloensis) fruit has interesting organoleptic properties, but its postharvest life is affected by gray mold decay caused by Botrytis cinerea. The effect of preharvest applications of methyl jasmonate (MeJA) or chitosan on the molecular defense-related responses and protection against gray mold decay were investigated in Chilean strawberry fruit during postharvest storage. Specifically, we inoculated harvested fruit with B. cinerea spores and studied the expression of genes enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 48 publications
3
30
0
1
Order By: Relevance
“…In strawberry, JA appears to be involved in defence responses against B. cinerea . For example, strawberries treated with MeJA had a delayed and much slower progression of B. cinerea infections (Saavedra et al , ; Zhang et al , ).…”
Section: Relevance Of Ripening Processes To Botrytis Cinerea Infectiomentioning
confidence: 99%
“…In strawberry, JA appears to be involved in defence responses against B. cinerea . For example, strawberries treated with MeJA had a delayed and much slower progression of B. cinerea infections (Saavedra et al , ; Zhang et al , ).…”
Section: Relevance Of Ripening Processes To Botrytis Cinerea Infectiomentioning
confidence: 99%
“…However, no visible necroses was observed in F. vesca plants upon spray treatment of chemicals or the mock treatment. Also, there are reports of spray treating strawberry plants with different chemicals to study induced resistance (Terry and Joyce, 2000;Eikemo, Stensvand and Tronsmo, 2003;Hukkanen et al, 2007;Landi et al, 2017;Saavedra et al, 2017). We therefore consider the observed effects to be the plant's induced responses to priming agent treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Sigma-Aldrich, #A44207-5G), R-β-homoserine (RBH, Aurum Pharmatech, #S-4676), and prohexadione-calcium (ProCa, Sigma, #31720) were dissolved in distilled H 2 O, methyl jasmonate (MeJ, Sigma-Aldrich, #392707) was prepared in 0.1% Tween-20, and gibberellic acid (GA3, Duchefa, #G0907.0001) was first dissolved in 50 µl ethanol and then diluted in H 2 O. Plants were treated in three different ways: (i) soil-drench using ten times concentrated (10×) solutions of the priming chemical(Jakab et al, 2005;Wilkinson et al, 2018), (ii) spray treatment of above-ground parts using final concentration (1×) chemical solutions(Saavedra et al, 2017), and (iii) treatment of seeds. For soil-drench treatments, 10× solutions were prepared corresponding to the concentrations given in the figure legends.Plants were treated by pouring 10% of the pot volume of the 10× solution into each pot.…”
mentioning
confidence: 99%
“…Other research showed that preharvest methyl jasmonate application reduced growth infection of B. cinerea in Chilean strawberries [F. chiloensis (L.) Mill.] through upregulation of the β-1,3-glucanase gene (FcBGs) and polygalacturonaseinhibiting protein (FcPGIP) gene (Saavedra et al, 2017). JA is associated with defense mechanisms against Alternaria altemata, Pseudomonas syringae, Hort.…”
Section: Discussionmentioning
confidence: 99%